The first draft of history: missing (media) fragments - Baraković, Vedada; Mevkić, Ajša (Historical Thought, 2025)
The aim of this paper is to research the role of mass media in mediating the treatment of witnesses / victims of violence in war crimes trials. The hypothesis of research in the paper is that mass media do not pay enough attention to the victims of violence. Furthermore, mass media trivial reporting and an (un)intentional victim identity revealing affect secondary victimization and re-traumatization of witnesses while, on the other hand, discourages anonymous victims of violence to testify. So numerous crimes remain unresolved, perpetrators remain unpunished, which all do not contribute to the process of dealing with past and reconciliation. In addition, even historical reconstruction of war period events can sometimes not be completed without the testimony of witnesses because material evidence of crime perpetrators are attempting to hide and to destroy so witnesses testimonies mediated by mass media remain the key proof of the crime, particularly considering the fact that testimonies besides a factual side often have an affective side which can be of particular importance in holistic observation of the context of historical events.